The effect of matrix on shape properties of aromatic disulfide based epoxy vitrimers - Azcune,I; Huegun,A; Ruiz,de Luzuriaga A; Saiz,E; Rekondo,A (European Polymer Journal, 2021)
Aromatic disulfide based vitrimers show elasticity driven shape-memory and plastic reprocessability via associative rearrangement of dynamic covalent crosslinks. Those processess represent the two sides of a coin: the storage and relaxation of the strain energy caused by a deformation load. The key temperatures that trigger the underlying mechanisms, i.e. phase transition and disulfide exchange reaction, are extremely sensitive to the molecular structure of the polymer and under certain condition overlap. To gain insight on the relationship between the structure, dynamic and shape-changing properties, five aromatic disulfide-based epoxy networks with a range of Tg values (32–142 °C), molecular structure and crosslink densities (2252–462 mol m−3) were synthesized. The epoxy matrices were formulated combining different ratios of rigid bisphenol A diglycidyl ether (DGEBA) and flexible poly(propylene glycol) diglycidic ether (DGEPPG) epoxy monomers crosslinked by 4-aminophenyldisulfide hardener.